Adrenal artery ablation for primary aldosteronism without apparent aldosteronoma: An efficacy and safety, proof‐of‐principle trial. Issue 9 (27th August 2020) - Zhang, Hexuan; Li, Qiang; Liu, Xiaoli; Zhao, Zhigang; He, Hongbo; Sun, Fang; Hong, Yangning; Zhou, Xunmei; Li, Yingsha; Shen, Rufei; Bu, Xiaona; Yan, Zhencheng; et al.
Abstract: Primary aldosteronism (PA) is associated with resistant hypertension and cardiovascular events. There are some limitations of current medical and surgical therapies for PA. To determine the efficacy and safety of catheter‐based adrenal artery ablation for treatment of PA patients who refused both surgery and medical therapy, we performed this prospective cohort study. Thirty‐six PA patients without apparent aldosteronoma were treated by adrenal artery ablation. Primary outcome was postoperative blood pressure and defined daily dose (DDD) of antihypertensive medications after adrenal ablation. Secondary outcome was biochemical success. We assessed outcomes based on Primary Aldosteronism Surgical Outcome (PASO) criteria. Adrenal CT scan, biochemical evaluation, adrenal artery ablation and adrenal venous sampling (AVS) were underwent. After adrenal ablation, complete clinical success (normotension without antihypertensive medication) was achieved in 9/36 (25.0%) patients and partial clinical success (reduction in blood pressure or less antihypertensive medication) in 13/36 (36.1%) patients. Complete biochemical success (correction of hypokalemia and normalization of aldosterone‐to‐renin ratio) was achieved in 16/36 (44.4%) patients. Office‐based and ambulatory blood pressures were reduced by 17/7 and 11/2 mmHg at 6 months after ablation, respectively. The plasma cortisol level in the ablation group decreased slightly, but no patient developed hypoadrenocorticism. Catheter‐based adrenal ablation appears to produce substantial and sustained blood pressure reduction and biochemical improvement, with only minor adverse events in PA patients without apparent aldosteronoma. This therapy could be an important supplement for current PA treatments.